2003
DOI: 10.1152/japplphysiol.00942.2002
|View full text |Cite
|
Sign up to set email alerts
|

Na+-K+-ATPase α2-gene and skeletal muscle characteristics in response to long-term overfeeding

Abstract: and skeletal muscle characteristics in response to long-term overfeeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…In addition, it seems that the enzyme is fully activated during exercise (41)(42)(43). The absolute OGDH activity values measured in skeletal muscle of adults in the present study was similar to those previously reported (42,44). However, to our knowledge, the activity of this enzyme has not yet been reported in children.…”
supporting
confidence: 91%
“…In addition, it seems that the enzyme is fully activated during exercise (41)(42)(43). The absolute OGDH activity values measured in skeletal muscle of adults in the present study was similar to those previously reported (42,44). However, to our knowledge, the activity of this enzyme has not yet been reported in children.…”
supporting
confidence: 91%
“…In addition, candidate genes in two of our linkage regions have previously been associated with obesity. These associations include the APOA2 (31,32) and ATP1A2 (33,34,35) genes located in our chromosome 1 linkage region () and SLC6A3 (36) located in one of our chromosome 5 (1–5 Mb) linkage regions ().…”
Section: Discussionmentioning
confidence: 99%
“…Body fatness‐related phenotypes (fat mass, percentage of body fat, sum of skinfolds) showed associations with markers in AGRP (87), AR (118), ATP1A2 (92), CNTFR (119), ESR1 (94), FOXC2 (96), IRS2 (101), LIPE (103), PPARA (109), and PPARG (113). Phenotypes reflecting body fat distribution (abdominal visceral fat, waist circumference, waist‐to‐hip girth ratio, sagittal diameter) were associated with ADRB2 (120, 121), APM1 (89), APOA1 (90), AR (122), CYP19A1 (123), DF (124), ESR1 (94), HSD11B1 (98), IL6 (99), IRS2 (101), LIPC (102), MACS2 (104), PPARG (113, 114), TGFB1 (117), and UCP1 (125).…”
Section: Qtls From Crossbreeding Experimentsmentioning
confidence: 99%